Literasi Digital pada Anak Usia Dini Upaya meningkatkan Pengetahuan tentang Dampak Kecanduan Handphone - Poppi Damayanti; Syahidin; Febrian Ahmad Dhani; Winaslis Armi (Yayasan Darussalam Bengkulu, 2025)
This community service aims to 1) provide information on the benefits and negative impacts of gadgets to children, 2) raise their awareness of the dangers of gadget addiction, and 3) equip Quranic recitation teachers at TPQ (Islamic boarding schools) with similar knowledge. The methods used included site surveys, coordination, and outreach. The activity was carried out at the Raudhatul Jannah Sukarami Mosque, Bengkulu City, on May 24, 2025, involving TPQ children and Quranic recitation teachers. The results showed an increase in participants' understanding of digital literacy and the risks of gadget use. A key finding was the high level of gadget and social media account ownership among children, although most are supervised. This activity emphasized the urgency of digital literacy and the collaborative role of forming a digitally aware and responsible generation.